Conductors, Semiconductors, Superconductors: An Introduction to Solid State Physics - Huebener, Rudolf P (Springer, 2016)
In the second half of the last century solid state physics and materials science experienced a great advance and established itself as an important and independent new field. This book provides an introduction to the fundamentals of solid state physics, including a description of the key people in the field and the historic context. The book concentrates on the electric and magnetic properties of materials. It is written for students up to the bachelor in the fields of physics, materials science and electric engineering. Because of its vivid explanations and its didactic approach, it can also serve as a motivating pre-stage and supporting companion in the study of the established and more detailed textbooks of solid state physics. The book is suitable for a quick repetition prior to examinations.